Reactive oxygen species production by human dendritic cells involves TLR2 and dectin-1 and is essential for efficient immune response against Mycobacteria - Romero, María Mercedes (2015)
Tuberculosis remains the single largest infectious disease with 10 million new cases and two million deaths that are estimated to occur yearly, more than any time in history. The intracellular replication of Mycobacterium tuberculosis (Mtb) and its spread from the lungs to other sites occur before the development of adaptive immune responses. Dendritic cells (DC) are professional antigen-presenting cells whose maturation is critical for the onset of the protective immune response against tuberculosis disease and may vary depending on the nature of the cell wall of Mtb strain. Here, we describe the role of the endogenous production of reactive oxygen species (ROS) on DC maturation and expansion of Mtb-specific lymphocytes. Here, we show that Mtb induces DC maturation through TLR2/dectin-1 by generating of ROS and through Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN) in a ROS independently manner. Based on the differences observed in the ability to induce DC maturation, ROS production and lymphocyte proliferation by those Mtb families widespread in South America, i.e., Haarlem and Latin American Mediterranean and the reference strain H37Rv, we propose that variance in ROS production might contribute to immune evasion affecting DC maturation and antigen presentation.